Crystal Structures and Magnetic Properties of Polyethylene Glycol (PEG-4000) Encapsulated Co0.5Ni0.5Fe2O4 Magnetic Nanoparticles - Edi Suharyadi; Lintang Griyanika; Joko Utomo; Ayu Kurnia Agustina; Takeshi Kato; Satoshi Iwata (Department of Physics, Sebelas Maret University, 2018)
Nanocrystalline mixed spinel ferrite of Co0.5Ni0.5Fe2O4 magnetic nanoparticles (MNPs) has been successfully synthesized by coprecipitation method and encapsulated by PEG-4000 with various concentrations. X-Ray Diffraction (XRD) patterns showed that nanoparticles contained Co0.5Ni0.5Fe2O4 spinel ferrite with crystallite size of 14.9 nm. After PEG-4000 encapsulation particles size decreased became 7.7 nm. Interaction Co0.5Ni0.5Fe2O4 nanoparticles with long chain PEG-4000 caused the crystal growth trap. Lattice parameter and X-Ray density have no significant difference after encapsulated PEG-4000. The coercivity (??) of Co0.5Ni0.5Fe2O4 was 214 Oe. The ?? decreased after PEG-4000 encapsulation became 127 Oe, which is due to the decrease of crystallite size. The maximum magnetization (Mmax) of Co0.5Ni0.5Fe2O4 was 12.0 emu/g, and decreased after PEG-4000 encapsulation to 11.7 emu/g, because PEG-4000 is paramagnetic. After the concentration of PEG-4000 increased, then the amount of paramagnetic material increase which lead maximum magnetization decrease.